2004
DOI: 10.1111/j.1464-410x.2004.04929.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial papillary urothelial carcinomas in young and elderly patients: a comparative study

Abstract: surgery only patients diagnosed with pT1 tumours were treated by intravesical bacille Calmette-Guérin (BCG) instillations; all received intravesical BCG if there was a recurrence. The clinicopathological variables, recurrence and disease-free interval to recurrence were assessed. Proliferative activity (MIB-1) and expression of cell-cycle regulation proteins cyclin D1, p53 and p27 kip1 were detected by immunohistochemistry in the tumours of both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 33 publications
4
42
2
6
Order By: Relevance
“…Interestingly, the opposite result was also reported. Migaldi et al have reported that women constituted 32 % of patients with age less than 45 years and 12 % amongst elderly patients aged ≥ 45 [8].However, in our study, We have not found any difference in gender distribution between younger and elder groups which is not in line with studies mentioned above. We have to point out that due to the fact that younger patients only account for a small part in all the studies, including our study, thus, it is difficult to conclude whether gender distribution in the two groups is different or not.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, the opposite result was also reported. Migaldi et al have reported that women constituted 32 % of patients with age less than 45 years and 12 % amongst elderly patients aged ≥ 45 [8].However, in our study, We have not found any difference in gender distribution between younger and elder groups which is not in line with studies mentioned above. We have to point out that due to the fact that younger patients only account for a small part in all the studies, including our study, thus, it is difficult to conclude whether gender distribution in the two groups is different or not.…”
Section: Discussioncontrasting
confidence: 76%
“…UBCs is typically a disease of older individuals, with the median age of the first diagnosis 69 and 71 years old for males and females respectively, and rarely occurs below the age of 40 years [7]. There is debate and uncertainty regarding the clinicopathologic characteristics of UBCs in younger patients [8][9][10][11][12][13]. Some studies reported a more favorable prognosis in young patients compared to old patients [14]; while other studies showed similar clinical course of UBCs in young and old patient groups [9,11].…”
Section: Introductionmentioning
confidence: 93%
“…Tumeurs urothéliales de la vessie chez les jeunes 1,5,6,[17][18][19] . L'aspect évolutif des TVNIM survenant entre 30 et 40 ans tend à se rapprocher de celui qui est noté chez les sujets âgés.…”
Section: Plusieurs Auteurs éVoquentunclassified
“…L'atteinte chez le jeune adulte (moins de 40 ans) est rare et ne dépasse pas 4 % selon les séries 1,2,[4][5][6][7] . L'évolution naturelle et le pronostic du carcinome à cellules transitionnelles (CCT) de la vessie chez les jeunes patients restent un sujet de débat et peu de données ont été publiées concernant cette entité.…”
Section: Introductionunclassified
See 1 more Smart Citation